A benefit evaluation model for build-up land use in megacity suburban districts. (December 2020) - You, Lie; Li, Yurui; Wang, Rui; Pan, Haozhi
Highlights: A population-economy-space and a 2-dimensional evaluation system are established. Efficiency is the focus of our model for suburban land use development. Suburban land use policy and developmental efficiency are examined for Tianjin, CN. Benefit improvement of suburbs has not paralleled population and economic growth. Multi-center structure of megacities has not been fully formed in the aspect of land use efficiency. Abstract: In the process of rapid development of megacities, existing cost-benefit evaluation for economic and ecological benefits of urban land use cannot be easily applied to evaluation of suburbs in megacities. In this paper, a benefit evaluation model is constructed to solve this problem on the basis of the "core-edge" theory. A "population-economy-space" triangular element evaluation system and a two-dimensional evaluation system are established. The method compares and differentiates suburban districts and central urban areas. Taking Tianjin, China as an example, this study carries out an empirical evaluation and applies the model to 11 suburban districts. The conclusions of the empirical evaluation are summarized as follows: (1) from the comparative results of similar suburban districts, the horizontal benefits in the districts above the development axis are higher than those in other districts; (2) from the comparative results between the central urban area and suburban districts, the land use benefit level of suburban districts has not increased with the increase in the total amount levels of population and economy, and some have a decreasing trend; (3) from the developmental patterns of suburban districts, most districts are under the model of marginal expansion, which reflects limitations of sub-center city planning and sprawling developmental pattern of build-up land. Our analytical models can facilitate the policy-making related to intensifying land use and optimizing land supply structure.